Institutions, Macroeconomic Policy and the growth of the Agricultural Sector in Nigeria. (Global Journal of Human-Social Science, 2012)
In this study we set out to examine the impact of institutional support and macroeconomic policy on the growth performance of the agricultural sector in Nigeria Data on relevant variables were collected from the Central Bank of Nigeria Statistical Bulletin 1970-2008 The data series were examined for unit roots and cointegration The series were characterized as 1 1 and are also cointegrated A model which relate the index of agricultural production to exogenous variables such as the volume of credit to the agricultural sector interest rate spread dummy for institutional reforms deficit financing were estimated using a cointegrating regression method The Fully Modified Ordinary Least Squares option was used in our regression The results indicate that the volume of credit to the agricultural sector deficit financing income GDP and institutional reform Dum were positively and significantly accounted for innovations in agricultural output for the period studied The interest rate spread has a negative relationship with agricultural output growth but not significant The study recommends liberalized interest rate policy and enhanced institutional support to the agricultural sector
Keywords: Institutions; Agricultural sector; Nigeria; Interest rate; cointegration; Growth